Cost‐effectiveness of diabetes screening initiated through a dental visit. Issue 3 (1st February 2017) - Neidell, Matthew; Lamster, Ira B.; Shearer, Barbara
Abstract: Objective: To analyse the cost‐effectiveness of a screening programme and follow‐up interventions for persons with dysglycemia who are identified during a dental visit. Methods: This study is a secondary analysis utilizing data from two relevant publications. Those studies identified persons with dysglycemia who were seen in a dental school clinic for routine dental care and determined compliance with a recommendation to seek medical care. The response site was 59.4%. The Archimedes disease simulation model was utilized to simulate the effect of a weight loss programme for identified subjects on several outcomes. Results: Two scenarios for weight loss programmes were considered: a 10% permanent loss in body weight and a 10% loss that decays over time. Both diabetes and prediabetes were analysed. The decay path costs $21 243 per quality adjusted life year (QALY) with 3 years required to achieve the weight reduction. This cost decreases to $6655 if only 1 year is needed to achieve the weight goal. Without decay, the cost per QALY is $15 873 with 20 years of intervention, vs $647 per QALY with 10 years of intervention. For individuals with type 2 diabetes mellitus, the cost per QALY is $48 604 to $56 207 depending on adherence. With the addition of oral medication (a sulfonylurea), the cost is three times higher. Conclusions: Under the conditions described here, identification of persons with dysglycemia in the dental office for initiating prediabetic care is a cost‐effective means of identifying and treating affected individuals.